2021
DOI: 10.1088/1361-6560/abe556
|View full text |Cite
|
Sign up to set email alerts
|

Interventional respiratory motion compensation by simultaneous fluoroscopic and nuclear imaging: a phantom study

Abstract: Purpose. A compact and mobile hybrid c-arm scanner, capable of simultaneously acquiring nuclear and fluoroscopic projections and SPECT/CBCT, was developed to aid fluoroscopy-guided interventional procedures involving the administration of radionuclides (e.g. hepatic radioembolization). However, as in conventional SPECT/CT, the acquired nuclear images may be deteriorated by patient respiratory motion. We propose to perform compensation for respiratory motion by extracting the motion signal from fluoroscopic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The phantom experiments showed that the SPECT image quality of IXSI was lower than that of a clinical scanner due to the placement of the flat panel detector in front of the gamma camera and the change from two to one detector head. However, in the case of imaging during radioembolization, it has through digital and experimental studies [9,[17][18][19] been demonstrated that IXSI can be expected to accurately retrieve various clinically and dosimetric important measures. The clinical performance of IXSI in other procedures is under active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The phantom experiments showed that the SPECT image quality of IXSI was lower than that of a clinical scanner due to the placement of the flat panel detector in front of the gamma camera and the change from two to one detector head. However, in the case of imaging during radioembolization, it has through digital and experimental studies [9,[17][18][19] been demonstrated that IXSI can be expected to accurately retrieve various clinically and dosimetric important measures. The clinical performance of IXSI in other procedures is under active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, a segmentation was applied by the threshold for different spheres with volumes from 10 mm to 37 mm of diameter, and the reported threshold values between 40% and 45% depending on the S/B ratio, volume and sphere diameter; similar parameters were used in this work. Considering these parameters is possible to apply this methodology in clinical studies, especially in treatments that imply respiratory motion [2], [17], perfusion in cardiology studies [3], radioembolization in liver with microspheres of 90Y [18], [19]. A threshold procedure is necessary for a correct image delineation in segmentation, including the area and volume delimitation to improve the resolution for SPECT/CT studies.…”
Section: Volume's Evaluation In Spect and Ctmentioning
confidence: 99%
“…One of the most common hybrid equipment in Nuclear Medicine services is the Single-photon Emission Computed Tomography (SPECT-CT) which allows the combination of the metabolic information provided by the volumetric image generated by the gamma camera (that allows the obtention of three-dimensional representations of the radiopharmaceutical distribution in the patient), and by the anatomical information provided by the Computer Tomography (CT) images. The use of phantoms represent a common practice in imaging acquisition procedures both for parameter setting and for radiopharmaceutical dosimetry evaluation (phantoms can be of different shapes, sometimes amorphous and with a defined form and unique characteristics, it depends of the body regions and organs on study) [2], [3]. Additionally, the organ motion produced by respiratory and cardiac movements is still a significant challenge for the accurate delivery of radiotherapy and diagnostics when using hybrid equipment [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…While the first three phenomena are routinely accounted for by reconstruction software, breathing motion is usually not corrected. Different methods have been proposed in the literature to retrieve and correct for breathing motion in SPECT images, e.g., using external breathing monitoring device [15], fluoroscopic images [16,17] or data-driven approaches [18,19]. Motion correction was, for example, applied to myocardial perfusion [20,21].…”
Section: Introductionmentioning
confidence: 99%